The soluble guanylate cyclase stimulator IW‐1973 prevents inflammation and fibrosis in experimental non‐alcoholic steatohepatitis. (31st January 2018) - Flores‐Costa, Roger; Alcaraz‐Quiles, José; Titos, Esther; López‐Vicario, Cristina; Casulleras, Mireia; Duran‐Güell, Marta; Rius, Bibiana; Diaz, Alba; Hall, Katherine; Shea, Courtney; Sarno, Renee; Currie, Mark; et al.
Abstract : Background and Purpose: Non‐alcoholic steatohepatitis (NASH) is the hepatic manifestation of metabolic syndrome and is characterized by steatosis, inflammation and fibrosis. Soluble guanylate cyclase (sGC) stimulation reduces inflammation and fibrosis in experimental models of lung, kidney and heart disease. Here, we tested whether sGC stimulation is also effective in experimental NASH. Experimental Approach: NASH was induced in mice by feeding a choline‐deficient, l ‐amino acid‐defined, high‐fat diet. These mice received either placebo or the sGC stimulator IW‐1973 at two different doses (1 and 3 mg·kg −1 ·day −1 ) for 9 weeks. IW‐1973 was also tested in high‐fat diet (HFD)‐induced obese mice. Steatosis, inflammation and fibrosis were assessed by Oil Red O, haematoxylin–eosin, Masson's trichrome, Sirius Red, F4/80 and α‐smooth muscle actin staining. mRNA expression was assessed by quantitative PCR. Levels of IW‐1973, cytokines and cGMP were determined by LC‐MS/MS, Luminex and enzyme immunoassay respectively. Key Results: Mice with NASH showed reduced cGMP levels and sGC expression, increased steatosis, inflammation, fibrosis, TNF‐α and MCP‐1 levels and up‐regulated collagen types I α1 and α2, MMP2, TGF‐β1 and tissue metallopeptidase inhibitor 1 expression. IW‐1973 restored hepatic cGMP levels and sGC expression resulting in a dose‐dependent reduction of hepatic inflammation and fibrosis. IW‐1973 levels were ≈40‐fold higher in liver tissue than in plasma. IW‐1973 also reduced hepatic steatosis and adipocyte hypertrophy secondary to enhanced autophagy in HFD‐induced obese mice. Conclusions and Implications: Our data indicate that sGC stimulation prevents hepatic steatosis, inflammation and fibrosis in experimental NASH. These findings warrant further evaluation of IW‐1973 in the clinical setting.